(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Perinatal mortality remains a significant global public health challenge, particularly in low- and middle-income countries, where the majority of stillbirths and early neonatal deaths occur. It serves as a sensitive indicator of the quality and accessibility of maternal, obstetric, and neonatal healthcare services. This review aims to analyze the prevalence of perinatal mortality, identify key risk factors contributing to its occurrence, and examine evidence-based strategies for its reduction. The findings indicate that major risk factors include preterm birth, low birth weight, birth asphyxia, severe neonatal infections, maternal complications during pregnancy and childbirth, inadequate antenatal and perinatal care, socioeconomic disadvantage, and limited access to quality healthcare services. Regional disparities are particularly evident in sub-Saharan Africa and parts of South and Central Asia, where perinatal mortality rates remain disproportionately high. The review highlights that effective reduction of perinatal mortality requires a comprehensive approach, including strengthening antenatal care, improving intrapartum and neonatal services, expanding the use of evidence-based interventions, enhancing health system infrastructure, and implementing regular perinatal audits. Addressing social determinants of health and reducing inequalities in access to care are also essential for achieving sustainable improvements in perinatal outcomes.